Diferenças no desenvolvimento de meninos e meninas em condição de risco - Almeida, Christiana Meira Gonçalves de; Rodrigues, Olga Maria Piazentin Rolim [UNESP]; Salgado, Manoel Henrique [UNESP] (My University, 2012)
This study aimed to evaluate the development of infants aged between 30 and 59 days, who presented some kind of risk factor threatening their development. Participated in the project 82 children, being 42 boys and 40 girls, presenting the following risk conditions: low birth weight, preterm birth or children of adolescent mothers. The protocol "Stimulation for kids" from "The Operationalized Portage Inventory" was administered. The girls presented a better performance in all conditions, however, no significant differences between genders were observed among the adolescent mothers' children. These results are consistent with those described in the literature and they indicate that the male population is more vulnerable to developmental damage. Public policies regarding early intervention to minimize the likelihood of future cognitive difficulties and consequently its impact in such population are essential.

Esse estudo teve como objetivo avaliar o desenvolvimento de bebês que possuíam alguma condição de risco. Participaram do projeto 82 crianças, 42 meninos e 40 meninas. Como critérios de inclusão definiu-se: baixo-peso ao nascer, parto pré-termo ou filhos de mães adolescentes Para avaliar o desenvolvimento foi utilizado o protocolo de "Estimulação Infantil" do Inventário Portage Operacionalizado, que foi aplicado entre 30 e 59 dias de vida do bebê. Em todas as condições as meninas tiveram melhor desempenho, porém na condição de filhos de mães adolescentes não foi observada diferença significativa entre os grupos. Os dados parecem indicar que as condições de risco possuem maior probabilidade de causar danos ao desenvolvimento à população masculina que à feminina, coerentes à literatura analisada. Análises e elaboração de programas de estimulação precoce constituem-se fundamentais para minimizar os riscos de problemas de desenvolvimento nessa população.
Boys and girls in risk conditions development differences
Keywords: Risk babies; Difference between gender; Operationalized portage inventory; Children development; Bebês de risco; Diferenças entre gêneros; Inventário portage operacionalizado; Desenvolvimento infantil